FORMATION OF FUTURE ENGINEERS ON THE BASIS OF HIGHER MATHEMATICS THROUGH THE USE OF INTEGRATED PROJECTS IN EDUCATION - Baratov Fayzullo Shukurovich (Journals Park Publishing, 2023)
Integrated Projects is a multidisciplial educational activity that integrates different disciplines such as math, science and engineering into a single project. These projects allow students to apply their knowledge and skills to solving real problems, develop critical thinking and problem-solving abilities.
Keywords: Engineering problems, bridge design, integrated, integrated education projects, Differential Accounting, Integral Account